THE EFFECT OF DIRECT CASH AID (BLT) DISTRIBUTION TOWARD INCOME AND POVERTY LEVEL IN INDONESIA - Indra Maipita (Jurnal Ilmiah Ekonomi Bisnis, 2012)
This study is purposed to analyze the impact of fuel subsidy reduction policy followed by the award of compensation in the form of BLT to the poor on income distribution and poverty. Computable General Equilibrium (CGE), Foster-Greer-Thorbecke (FGT index) and betha density distribution function model analysis was used to achieve the goal. The results showed that the reduction in fuel subsidies, followed by the compensation of direct cash aid (BLT) to the poor households have an impact on increasing poverty, income inequality and poverty severity. In other words, the impact of direct cash aid (BLT) to the poor households is unable to offset the impact caused by the reduction in fuel subsidies.   Keywords: Subsidies, Direct Cash Aid (BLT), Income and Poverty